Relationship Between the Level of Knowledge and Attitude Towards Maternal Behavior of Stunting Prevention at Bojong Nangka Community Health Center in Tangerang District - Tanara, Arron; Rivami, Dwi Savitri (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Background: Stunting is one of the major health problems in Indonesia. In 2022, the prevalence of stunting in Indonesia was 21.6%, and there were still 9,200 cases of stunting in Tangerang District alone. Stunting prevention can be done since pregnancy. It is estimated that stunting prevention behaviors among pregnant women is related to their knowledge and attitudes. Puskesmas Bojong Nangka was a community health center in Tangerang that treated stunting but has no data on this matter. Methods: This study used a cross-sectional study design. Data on the level of knowledge, attitudes, and behaviors in stunting prevention was collected using questionnaires and further was analyzed using the Chi-square test. Result: From 96 respondents, it was found that the majority (63.5%) had a good level of knowledge on stunting prevention. Most respondents also had a good attitude towards stunting prevention (83.3%). There were 72 respondents (75%) who had recommended stunting prevention behaviors. Bivariate analysis showed that there was a significant relationship between knowledge level and stunting prevention behaviors (P value < 0.001; OR 7.29; 95% CI 2.6 – 20.39) but there was no significant relationship between attitudes and stunting prevention behaviors (P value = 1; OR 1; 95% CI 0.29 – 3.45). Conclusions: There was a significant relationship between the level of knowledge towards stunting prevention behaviors among pregnant women at Bojong Nangka Community Health Center, Tangerang District.